A 3‐year controlled clinical trial comparing high‐translucency zirconia (cubic zirconia) with lithium disilicate glass ceramic (e.max) - Hiba A. Fawakhiri; Souad Abboud; Shaza Kanout (Wiley, 2023)
Abstract Introduction The rate of clinical success in veneers, under esthetics, has achieved a range of 18 months to 20 years. In a plethora of studies, it registers a success rate reaching 75% and even 100%. The most common type of glass ceramics used in ceramics is the vitreous lithium disilicate crystal‐reinforced material, e.max®. Recent studies focus on "polycrystalline ceramic use" in manufacturing veneers, as it possesses a stronger structure and different enabling manufacturing schemes. Objectives This research aims at comparing e.max and the high‐translucent Cubic Zirconia. Such comparison is administered to veneers manufacturing: esthetic (surface and edge, and staining and color matching), functional (crack and fracture, contact point, and patient satisfaction), and biological (posttreatment vitality and hypersensitivity, and periodontal response). Materials and Methods The research sample consisted of 60 veneers, divided into two groups: cubic zirconia and e.max. The sample included 2 males (16.6%) and 10 females (83.3%), with age ranging from 25 to 37 years. Patients were thoroughly diagnosed and treated and included in this study based on certain inclusion-exclusion criteria. Hickel's 2010 criteria were utilized to examine and observe the clinical aspect of veneers during intervals of 1 week, 3 months, 1 year, and 3 years. Results No significant differences were traced across the groups for all the variables, with a p‐value being greater than 0.05. The e.max group revealed better clinical results compared to the cubic zirconia one regarding esthetics and tooth translucency. Nonetheless, the results showed a merely slight increase in hypersensitivity in the e.max group. Conclusion Within the limitation of an extensive follow‐up period, we can conclude that there is no difference between cubic zirconia and e.max (p > 0.05), where e.max and cubic zirconia veneers have the same characteristics in terms of the following. The characteristics of the aspects examined were esthetic, functional, and biological.